(untitled) (Journal of the College of Education for Women, 2019)
The judgment enjoys many potential sources. If we look at these sources with analytical view that enable us to identify the potentials of strength in them which is the existence of features that distinct each place from the other one, which can be considered opportunities that provide the designer and the planner the possibility to design and planning which is based on subs taken from the reality of the available data of the location.At this point outstands the role of development sources as one of the processes of re-configuring the place which appear as a result of a reality that requires setting new goals for the society and to achieve these goals it takes observations dealing with the place policies that should be taken, so this research will focus on data analysis using the quantitative methods which are represented in:1- Analysis of development potentials.2- Price weighted index method.To suggest a development policy for the area of the study compatible with its developmental capacities taking in consideration the following main pillars while putting the regional development policy:1- Development sources and their limitations in the area of study.2- Identifying the factors influencing the development process .A- The factor of multiple sources: ( human, demographical, educational, health, and general facilities.)